How much sleep does an elite athlete need? - Sargent, C.; Lastella, M.; Halson, S. L.; Roach, G. D. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Anecdotal reports indicate that many elite athletes are dissatisfied with their sleep, but little is known about their actual sleep requirements. Therefore, the aim of this study was to compare the self-assessed sleep need of elite athletes with an objective measure of their habitual sleep duration.